2019
DOI: 10.1016/j.bbr.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress disrupts social behavior, cortical neurobiology and commensal microbes in adult male offspring

Abstract: In utero and early neonatal exposure to maternal stress is linked with psychiatric disorders, and the underlying mechanisms are currently being elucidated. We used a prenatal stressor in pregnant mice to examine novel relationships between prenatal stress exposure, changes in the gut microbiome, and social behavior. Here, we show that males exposed to prenatal stress had a significant reduction in social behavior in adulthood, with increased corticosterone release following social interaction. Male offspring e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 53 publications
(72 reference statements)
8
70
1
Order By: Relevance
“…Furthermore, unlike other models 68 , mRNA transcripts of inflammatory signaling molecules within uterine tissue were not altered in our model. Even still, our previous observations demonstrate significant impacts of gestational restraint stress on offspring inflammation and behavior 25,42 , which are largely CCL2dependent 43 . Altered production and expression of CCL2 and CCR2 in both the fetal brain and placenta coincide with pro-inflammatory signatures within these tissues and appear to drive offspring sociability 43 .…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Furthermore, unlike other models 68 , mRNA transcripts of inflammatory signaling molecules within uterine tissue were not altered in our model. Even still, our previous observations demonstrate significant impacts of gestational restraint stress on offspring inflammation and behavior 25,42 , which are largely CCL2dependent 43 . Altered production and expression of CCL2 and CCR2 in both the fetal brain and placenta coincide with pro-inflammatory signatures within these tissues and appear to drive offspring sociability 43 .…”
Section: Discussionmentioning
confidence: 79%
“…In animal models, systemic administration of particular cytokines in circulation, such as IL-6 and IL-1β, is sufficient to recapitulate specific offspring neuroimmune abnormalities seen with prenatal stress 59,60 . Interestingly, while psychological stress is thought to induce cytokine production in animal models (and is frequently described in placental and offspring brain tissue, including by our group 25,42 ), few, if any, studies have reported maternal circulating cytokine levels. Here, we found a decrease in IL-5 and a trending decrease in CCL2 in maternal circulation, and none of the suspected increases in IL-6 and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations